ART adherence clubs in the Western Cape of South Africa: what does the sustainability framework tell us? A scoping literature review. Issue 3 (19th March 2019) - Flämig, Kornelia; Decroo, Tom; van den Borne, Bart; van de Pas, Remco
Abstract: Introduction: In 2007, the antiretroviral therapy (ART) adherence club (AC) model was introduced to South Africa to combat some of the health system barriers to ART delivery, such as staff constraints and increasing patient load causing clinic congestion. It aimed to absorb the growing number of stable patients on treatment, ensure quality of care and reduce the workload on healthcare workers. A pilot project of ACs showed improved outcomes for club members with increased retention in care, reduced loss to follow‐up and a reduction in viral rebound. In 2011, clubs were rolled out across the Cape Metro District with promising clinical outcomes. This review investigates factors that enable or jeopardize sustainability of the adherence club model in the Western Cape of South Africa. Methods: A scoping literature review was carried out. Electronic databases, organizations involved in ACs and reference lists of relevant articles were searched. Findings were analysed using a sustainability framework of five key components: (1) Design and implementation processes, (2) Organizational capacity, (3) Community embeddedness, (4) Enabling environment and (5) Context. Results and Discussion: The literature search identified 466 articles, of which six were included in the core review. Enablers of sustainability included the collaborative implementation process with collective learning sessions, the programme's flexibility, the high acceptability, patient participation and political support (to some extent). Jeopardizing factors revolved around financial constraints as non‐governmental organizations are the main supporters of ACs by providing staff and technical support. Conclusions: The results showed convincing factors that enable sustainability of ACs in the long term and identified areas for future research. Community embeddedness of clubs with empowerment and participation of patients, is a strong enabler to the sustainability of the model. Further policies are recommended to regulate the role of lay healthcare workers, ensure the reliability of the drug supply and the funding of club activities.